Influence of variation of liquidity in asset pricing: panel analysis of the brazilian market for the period january 2000 to june 2008 - Vieira, Kelmara Mendes (2011)
The influence of liquidity on return on assets has been subject of much research in recent years, from the point of view of individual assets as well as considering the liquidity of the market as a whole. This study aims to evaluate the influence of change in liquidity in the pricing of assets. The measures of liquidity consisted of variations in the quantity of securities, in the number of trades and in financial volume, as well as these variables weighted by the Bovespa index and also the same variables lagged. The sample is made up of the shares traded in the São Paulo Stock Exchange. Monthly data were collected for the period of January 2000 through June 2008. The results show that return on assets is positively influenced by the Bovespa index and by variations in liquidity. In general, it is the companies with the lower liquidity levels that show the highest positive variations of their own liquidity, therefore, having higher returns.